BAHASA PADA PEMBERITAAN INDONESIA-MALAYSIA: Analisis Bahasa Berita tentang Malaysia di Televisi Swasta Indonesia - Bonaventura Satya Bharata (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2022)
This article tries to describe how the language of television journalism in Indonesia constructs news about Malaysia. The news reviewed is news about territorial disputes, cultural claims, and Malaysia's treatment of Indonesian migrant workers or Indonesian citizens. Meanwhile, the news programs studied were Metro Highlight from Metro TV and Liputan 6 from SCTV. This research used a framing analysis method to study news. The results showed that both Metro Highlight and Liputan 6 did framing by selecting facts, diction, and images. Compared to Metro TV, which mostly uses diction in the form of language style, Liputan 6 SCTV uses more straightforward diction. Metro TV displays a lot of provocative images. Liputan 6 SCTV displays more pictures that cool the atmosphere. Metro TV provides a special time for news about Malaysia through the Metro Highlight program, while Liputan 6 SCTV announces it as part of the regular program.